Eficiența guvernării în susținerea dezvoltării umane - Mărginean, Ioan; Ciucă, Vasilica; Lazăr, Mitica; Moldoveanu, Maria; Munteanu, Carmen; Nica, Raluca; Novac, Andrei; Precupețu, Iuliana; Preda, Marian; Prisăcaru, Corneliu; Stanciu, Mariana; Voinea, Lăcrămioara (Calitatea Vieții, 1997)
Without abstract